O programa Minas Mundi e a participação de alunos de baixa renda: o mundo é mesmo logo ali? - Larissa Maria Rodrigues de Oliveira (2022)
The students’ assistance policies gain centrality in the context of enlargement and expansion of higher education in the 21st century. Among these policies’ objectives, is the guarantee of inclusion of those students who, due to socio-economic conditions, are prevented or deprived from accessing certain programs, services, or opportunities that the university offers. This paper aims to address the participation of students from low-income families in the main mobility program from UFMG between the years 2010 to 2018, the Minas Mundi. Thus, the creation of the Program developed by the institution is analyzed. It is considered that this Program did not find parameters in proportions and coverage, in no Brazilian public university, as for the participation of students from low social-economic status. The academic mobility also appears in the discussion as a practice intrinsic to the university, however, in the recent decades, has stood out in the Brazilian universities under the guidance of an agenda determined by multilateral organizations for higher education. Further on the critic discussion regarding international mobility and the expansion of higher education in Brazil in the last three decades, the work develops a documental analysis of the Minas Mundi Program Announcements, of the PDI’s from 2008, 2013 and 2018, the Management Reports from 2005 to 2020, monitoring the evolution and modification promoted on the Program throughout the years, seeking to identify proposals and actions turned and/or that enabled the inclusion and participation of low-income students in the Program. It is worth mentioning the difficulties in accessing data during the most critical period of Covid-19, both of those that could have been organized in the Department of International Relations, as well as the documents from other divisions of the university involved in the process of socio-economic analysis and of scholarships’ distribution. It is concluded that, even with the increase of the numbers of vacancies offered, from partner universities and participating students, the resources spent were insufficient for the effective inclusion of low-income students.